ETHANOL INHIBITION OF DOPAMINE TRANSMISSION IN ANIMAL MODELS OF ALCOHOL ABUSE LIABILITY - Yorgason, Jordan Thomas (Wake Forest University, 2013)
Mesolimbic dopamine neurons, originating in the ventral tegmental area (VTA) and projecting to the nucleus accumbens (NAc), have been heavily implicated in the reinforcing and rewarding properties of natural and drug rewards and cues that predict these rewards. Ethanol's effects on dopaminergic activity are bimodal, and can be thought of in terms of a balance between excitation and inhibition. While low to moderate doses (0.25-1 g/kg, I.P.) of ethanol result in increases in dopamine levels as measured by microdialysis, dopamine levels are slightly attenuated at higher ethanol doses (2 g/kg, I.P.), and reduced at even higher, sedating doses of ethanol (5 g/kg, I.P). In vivo voltammetry studies, which describe dopamine overflow on a sub-second time scale, have also shown ethanol-mediated inhibition of dopamine release, although at considerably lower doses (1-2 g/kg, I.P.). NAc slice voltammetry studies have also shown reductions in dopamine release after ethanol, albeit only at extremely high, supraphysiological concentrations (>150 mM; roughly equivalent to 7.5 g/kg, I.P.). From these in vivo and ex vivo voltammetry experiments, the authors of these previous studies hypothesized that ethanol's primary site of inhibition occurs at dopamine cell bodies, which are absent in coronal striatal slices. However, another major difference between these voltammetry studies are the stimulation paradigms used for evoking dopamine release, which may represent two functionally different modes of firing for dopaminergic neurons. High frequency dopamine stimulations (>14 Hz) are used to model rapid `phasic' firing of dopamine neurons, whereas low frequency stimulations (<10 Hz) are used to model `tonic' pacemaker firing. The results in CHAPTER II describe our primary parametric experiments examining ethanol inhibitory effects across a range of stimulation parameters. Ethanol inhibition potency was increased under high frequency (20-125 Hz) multiple pulse (5-10 pulses) conditions suggesting that ethanol inhibition is greatest under phasic dopamine release conditions. Increased ethanol sensitivity under high frequency conditions was not due to the amount of dopamine release, as reductions in stimulation intensity, and calcium levels, which both result in reduced release, still resulted in increased sensitivity compared to single pulse release.
Keywords: accumbens; dopamine; early life stress; ethanol; voltammetry; vulnerability